2013
DOI: 10.1186/1471-2229-13-204
|View full text |Cite
|
Sign up to set email alerts
|

TcNPR3 from Theobroma cacao functions as a repressor of the pathogen defense response

Abstract: BackgroundArabidopsis thaliana (Arabidopsis) NON-EXPRESSOR OF PR1 (NPR1) is a transcription coactivator that plays a central role in regulating the transcriptional response to plant pathogens. Developing flowers of homozygous npr3 mutants are dramatically more resistant to infection by the pathogenic bacterium Pseudomonas syringae, suggesting a role of NPR3 as a repressor of NPR1-mediated defense response with a novel role in flower development.ResultsWe report here the characterization of a putative NPR3 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 53 publications
1
34
0
Order By: Relevance
“…To test the efficacy of the proteins in cacao leaves, we developed an Agrobacterium-mediated transient gene expression system (agro-infiltration) capable of expressing substantial amounts of the proteins in a large percentage of leaf cells (Shi et al, 2013). The transgenes were driven by a very strong modified E12-Ω CaMV35S promoter (Mitsuhara et al, 1996).…”
Section: Transient Expression Of Pi-p-binding Domainsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test the efficacy of the proteins in cacao leaves, we developed an Agrobacterium-mediated transient gene expression system (agro-infiltration) capable of expressing substantial amounts of the proteins in a large percentage of leaf cells (Shi et al, 2013). The transgenes were driven by a very strong modified E12-Ω CaMV35S promoter (Mitsuhara et al, 1996).…”
Section: Transient Expression Of Pi-p-binding Domainsmentioning
confidence: 99%
“…For transient transformation of detached cacao leaves, A. tumefaciens cells containing each transgene were grown as described in Maximova et al (2003), induced with acetosyringone, and then vacuum-infiltrated into stage C leaves from cultivar Scavina6 as described in Shi et al (2013). The Petri dishes were sealed and incubated at 25°C for 2 days with light intensity of 145 m 2 /s and 14-h daylight.…”
Section: Transient and Stable Transformation Of T Cacaomentioning
confidence: 99%
“…Accordingly, genetic analysis demonstrated that mutation of NPR1 results in decreased expression of defense response genes and increased susceptibility to pathogens (Cao et al ., ; Volko et al ., ; Dong, ; Yan and Dong, ), while NPR3 and NPR4 negatively regulate the pathogen resistance and a gain‐of‐function npr4 mutant repressed the immune responses constitutively in Arabidopsis (Zhang et al ., ; Ding et al ., ). Such a negative role of NPR3 was also reported with the TcNPR3 gene from cacao (Shi et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Specific primers for P. tropicalis Actin (F: GACAACGGCTCCGGTATGTGCAAGG and R: GTCAGCACACCACGCTTGGACTG) and cacao Actin 7 (Tc01g010900) (F: AGGTGGAGATCATTGAAGGAGGGT and R: ACCAGCGGTCATCACAAGTCACAA) genes were used as pathogen and host targets. qPCR was performed using an ABI 7300 (Applied Biosystems, Foster City, CA, USA) as previously described ( Shi et al , 2013 ). Differences between genotypes and treatments were identified using Fisher’s partial least-squares difference analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence suggests that T. cacao also uses the SA-dependent pathway during defence responses ( Borrone et al , 2004 ; Bailey et al ., 2005 a , b ; Maximova et al , 2006 ; Gesteira et al , 2007 ), and PR genes are up-regulated in leaves after treatment with the SA analogue BTH ( Verica et al , 2004 ). Moreover, genes encoding cacao homologues of NPR1 (Tc09_g007660) and NPR3 (Tc06_g011480) can partially restore the Arabidopsis npr1 and npr3 mutant phenotypes, demonstrating the highly conserved nature of this signalling pathway ( Shi et al ., 2010 , 2013 ). In contrast, the transcriptional responses of Theobroma cacao cultivar ‘Comum’ to infection by WBD did not include significant changes in the transcription of genes in the SA pathway although there was activation of a variety of other genes implicated in defence responses and repression of photosynthesis ( Teixeira et al , 2014 ), implying that the SA pathway may not be the predominant mechanism of response to this particular pathogen or in this cultivar.…”
Section: Introductionmentioning
confidence: 99%